Engineered Extracellular Matrices with Integrated Wireless Microactuators to Study Mechanobiology. Issue 40 (7th August 2021) - Uslu, Fazil E.; Davidson, Christopher D.; Mailand, Erik; Bouklas, Nikolaos; Baker, Brendon M.; Sakar, Mahmut Selman
Abstract: Mechanobiology explores how forces regulate cell behaviors and what molecular machinery are responsible for the sensing, transduction, and modulation of mechanical cues. To this end, probing of cells cultured on planar substrates has served as a primary experimental setting for many decades. However, native extracellular matrices (ECMs) consist of fibrous protein assemblies where the physical properties spanning from the individual fiber to the network architecture can influence the transmission of forces to and from the cells. Here, a robotic manipulation platform that allows wireless, localized, and programmable deformation of an engineered fibrous ECM is introduced. A finite‐element‐based digital twin of the fiber network calibrated against measured local and global parameters enables the calculation of deformations and stresses generated by different magnetic actuation schemes across a range of network properties. Physiologically relevant mechanical forces are applied to cells cultured on the fiber network, statically or dynamically, revealing insights into the effects of matrix‐borne forces and deformations as well as force‐mediated matrix remodeling on cell migration and intracellular signaling. These capabilities are not matched by any existing approach, and this versatile platform has the potential to uncover fundamental mechanisms of mechanobiology in settings with greater relevance to living tissues. Abstract : An in vitro biomimetic platform that provides independent control over geometry, mechanics, and structure over extracellular matrices is introduced. Remote application of forces using robotically controlled magnetic microactuators triggers native mechanobiology responses including intracellular signaling and directed migration. A digital twin complements the platform by reporting stresses generated upon actuation.